Optimizing the nanoimprinting process of copper - Yeo, Kai Cheng (Nanyang Technological University, 2020)
Due to the versatility of nanowires, fabrication processes have been widely researched on. There are many protocols available for the fabrication of nanowires, but most require long hours and high cost. Ultrasonic embossing is the fabrication technique used for the purpose of this project. It exploits high frequency mechanical vibrations to extrude the nanowires in a template-based one step process. Copper at room temperature is too hard for the nanoimprinting process and might need the presence of heat to soften it before the experiment. However, copper oxidises easily at elevated temperatures. Therefore, there is a need to perform the fabrication process in an inert atmosphere. This project aims to further improve the nanoimprinting-ultrasonic embossing fabrication process by including a heating plate and minimising the oxidation of copper by introducing argon during the embossing process. Lubrication will not be used in the fabrication process; the parameters and their corresponding results will then be investigated. The nanoimprinting process was successfully optimized with the modification of the experimental setup and a further understanding of the experimental procedures. Bigger and uniform areas of copper nanowires were able to be fabricated.